1998
DOI: 10.1164/ajrccm.157.2.97-02039
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Invasive and Noninvasive Quantitative Culture Sampling on Outcome of Ventilator-Associated Pneumonia

Abstract: We performed an open, prospective, randomized clinical trial in 51 patients receiving mechanical ventilation for more than 72 h, in order to evaluate the impact of using either invasive (protected specimen brush [PSB] and bronchoalveolar lavage [BAL] via fiberoptic bronchoscopy) or noninvasive (quantitative endotracheal aspirates [QEA]) diagnostic methods on the morbidity and mortality of ventilator-associated pneumonia (VAP). Patients were randomly assigned to two groups: Group A patients (n = 24) underwent Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
161
0
15

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(185 citation statements)
references
References 26 publications
(30 reference statements)
7
161
0
15
Order By: Relevance
“…This would support the concept that deeper specimens would be more reliable than upper airway secretions. The use of semiquantitative cultures of tracheal aspirates was as good as deeper samples in one pilot study [39], the group had previously shown that the endotracheal aspirate was not as specific as deeper samples [40]. Therefore, their pilot study may not adequately answer the question of whether invasive specimens are necessary.…”
Section: Discussionmentioning
confidence: 96%
“…This would support the concept that deeper specimens would be more reliable than upper airway secretions. The use of semiquantitative cultures of tracheal aspirates was as good as deeper samples in one pilot study [39], the group had previously shown that the endotracheal aspirate was not as specific as deeper samples [40]. Therefore, their pilot study may not adequately answer the question of whether invasive specimens are necessary.…”
Section: Discussionmentioning
confidence: 96%
“…In the three, randomized, controlled Spanish studies, no differences in mortality and morbidity were found when either invasive (PSB and/or BAL) or QEA techniques were used to diagnose VAP (175,176,186). However, these studies contained relatively few patients (51, 76, and 88 patients) and therefore were not powered sufficiently to demonstrate a difference in mortality.…”
Section: Microbiologic Diagnosismentioning
confidence: 97%
“…Three comparatively small single centre studies comparing mortality in patients with suspected VAP managed on the results obtained by either invasive studies or quantitative analysis of tracheal aspirates failed to find any difference in mortality. 55 58 61 A much larger study involving 413 patients suspected of having VAP suggested that an invasive diagnostic strategy was desirable. 59 Compared with patients who received clinical management, patients who received invasive management had reduced mortality rate at day 14 (16.2% and 25.8%, p = 0.02) and decreased antibiotic use (mean (SD) number of antibiotic free days, 5.0 (5.1) and 2.2 (3.5), p,0.001).…”
Section: Microbiological Diagnosismentioning
confidence: 99%